Indonesia’s Active, Creative, Effective and Joyful Learning: From a University Teacher Training Program to High School Classrooms - MICHAEL SEAN YOUNG (Indonesian Research Journal in Education |IRJE|, 2018)
This study asked how and to what extent professors were modeling and encouraging active-learning methods in the students’ English and Education courses in response to decentralization reforms at the University of Banten, in Serang, Indonesia. A discussion of the background of PAKEM (pembelajaran aktif, kreatif, efektif dan menyenangkan) policy and its implementation builds a framework for identifying and interpreting specific challenges which impact English teacher preparation and the knowledge and implementation of PAKEM Active Learning methods. PAKEM represents a major element of ongoing decentralization policy and was explored thematically through an ethnographic analysis of in-depth accounts of professors, teachers, and students at the campus over ten months. The discussion provides extensive and diverse evidence of dynamic responses to PAKEM policy changes. Lecturers were well informed about and engaged in the implementation of active learning methods in instruction. Findings are situated amongst similar case studies on the implementation of active learning pedagogies and consistencies are identified and discussed.